Case series of immunosuppressant drug interactions with flucloxacillin in heart transplant recipients. (11th September 2019) - Gellatly, Rochelle M; Yoo, Sookyung; Bergin, Peter; Leet, Angeline
Abstract: Background: After heart transplantation, the International Society for Heart and Lung Transplantation (ISHLT) recommends calcineurin inhibitor (CNI)‐based immunosuppressant therapy with mycophenolate or a mammalian target of rapamycin (mTOR) inhibitor. Both CNIs and mTOR inhibitors are extensively metabolised by the cytochrome P450 enzyme pathway and are substrates of P‐glycoprotein (PGP), making drug interactions with these therapies an important consideration. Herein we report four cases of probable drug interactions between tacrolimus and everolimus with flucloxacillin in orthotopic heart transplant recipients. The effects were subtherapeutic immunosuppressant concentrations and cellular rejection. Clinical details: All four heart transplant recipients received intravenous (IV) flucloxacillin for methicillin‐sensitive Staphylococcus aureus infections in conjunction with immunosuppression regimens containing everolimus and/or tacrolimus. Despite tacrolimus and everolimus dose adjustments, Grade 2R rejection was diagnosed in all four patients in association with subtherapeutic immunosuppressant concentrations. Outcomes: A considerable increase in tacrolimus and everolimus trough concentrations was observed following cessation of IV flucloxacillin. The rise in concentrations occurred despite no change in or dose reductions of immunosuppressants. A possible mechanism for the interaction is via pregnane X receptor activation. Conclusion: These cases provide support that flucloxacillin significantly reduces tacrolimus and everolimus trough concentrations in heart transplant recipients. Dosage adjustments and close monitoring of drug concentrations or consideration of alternative antimicrobial therapy is required to avoid episodes of rejection or adverse events upon commencing and ceasing flucloxacillin therapy.